Epichloë typhina from toxic tall fescue grasses. - Bacon, C W (1977)
Epichloë typhina, a clavicipitaceous systemic phytopathogen, was isolated from two varieties and three hybrids of tall fescue (Festuca arundinaceae). The morphology of the fescue isolates was compared with E. typhina isolated from bent grass (Agrostis perennans). In all isolates, conidia were identical and were typical of E. typhina. In fescue grasses the endophyte failed to produce stromata, but on bent grass the fungus seasonally produced stromata, typical of the genus. Cattle grazing the fescue grasses showed signs of the fescue toxicity syndrome, the E. typhina was found in frequencies of 100%; in grasses from pastures in which cattle showed no signs of the syndrome, frequencies were 0 to 50%. Nutritional factors in vitro were more complex for the isolates from fescue than for the isolate from bent grass. These studies suggested that E. typhina includes biotypes that might be involved in the toxicity syndrome. The fescue biotypes grew poorly on media, and yields were inadequate for toxicity studies. However, the bent grass isolate grew well on three media, and extracts from two of these were toxic to chicken embryos. All isolates produced in vitro the nontoxic fungal steroid tetraenone [ergosta-4,6,8(14),22-tetraen-3-one], which has been isolated from toxic fescue grasses.